Effectiveness of peripheral neurectomy in refractory cases of trigeminal neuralgia - Narayan Sharma Lamichhane; Xiaoyan Du; Shanchang Li; Dhruba Chandra Poudel (Wolters Kluwer Medknow Publications, 2016)
Context: Trigeminal neuralgia (TN) is a commonly diagnosed neurosensory disease of orofacial region involving the fifth cranial nerve. Patient refractory to pharmacotherapy or with clinical and/or laboratory side effects sufficient to demand drug cessation is subjected to surgical technique. Aims: The aim of this study is to investigate the efficacy of peripheral neurectomy in the management of refractory TN. Settings and Design: This retrospective study on forty patients refractory to carbamazepine was conducted in the department of oral and maxillofacial surgery in the Northeast part of China from September 2011 to September 2014. Patients and Methods: Patients treated with neurectomy were followed up at regular intervals to assess the duration of pain-free period, and the pain was assessed using visual analog scale and the success of the surgery was defined accordingly. Statistical Analysis Used: Descriptive statistical analysis was carried out using IBM SPSS-20. Results: The mean age of the patients was 67.92 years (46-86 years), with higher incidence in females (F:M = 1.6:1). The 3rd division of trigeminal nerve was most commonly affected by the disease. The right side was more common than the left side. Duration of postsurgical pain-free period varied from 12 to 36 months with mean pain-free duration of 23.25 months. Recurrent cases were treated with low dose of carbamazepine, and majority of them were relieved of symptoms. Conclusions: Peripheral neurectomy is a minimal invasive surgery; safe and effective for elderly patients, especially in rural areas where advanced neurosurgical facilities are not available and for those who are reluctant to major neurosurgical procedures.